خارج الجسم الحي Vitis vinifera L. الأكثار الدقيق لثلاثة اصناف من العنب الاوربي - ابراهيم كاظم محمد; رشيد خليل ابراهيم; خليل ثامر حميد (Al-Nahrain Journal of Science, 2012)
In vitro techniques were used for the propagation of three grape varieties. They were Ollivate blane, Halawani and Kamali. The effects of Benzyl adenine (BA) and Kinetin (Kin) were studied on shoot number and height. Browning phenomenon in nutrient medium was treated by adding 100 mg/l of ascorbic acid with 150 mg/l of citric acid then soaking the explants for 24 hours in water before culture. BA of 1 mg/ l affected shoot multiplication, reaching to 2.6, 2.4 and 2.4 shoot/ explant formed from single nodes, and 2.4, 2.3 and 2.2 shoot/explant for those formed from shoot tips. Kin at 0.1 mg/l gave 2.4, 2.4 and 2.2 shoot/ explant for the three varieties respectively. Among the three propagation media tested during acclimatization, which were peat moss, peat moss: sand (1:1) and sand only, the peat moss: sand achieved the highest survival rate reaching 80% especially when combined with plantlet covering with plastic. Irrigation with ½ or ¼ strength MS salts improved subsequent plants growth